Predicting punitive attitudes to sentencing: does the public's perceptions of crime and Indigenous Australians matter? - Brookman, Ruth P. (The Australian and New Zealand journal of criminology, 2017)
In English-speaking western cultures the punitive attitudes towards law-breakers is well documented. The present study examines the utility of predictors of punitive attitudes with online survey data obtained from a convenience sample of 566 Australian residents. After controlling for demographic variables, the study examines the utility of two theoretical models; the Crime-distrust model and the Racial-animus model, in predicting punitive attitudes. All three factors of the Crime-distrust model significantly predict punitive attitudes. The study extends the current literature through identifying the significance of negative perceptions of Indigenous Australians in predicting punitive attitudes to sentencing. Results suggest that community perception of Indigenous Australians is a significant predictor of punitive attitudes in addition to factors of the Crime-distrust model. Future research using a more representative sample of the Australian population is recommended to increase the confidence with which findings are interpreted.